The Role of Financial Services Authorities in Strengthening the Banking Industry in Indonesia (Study During the Covid-19 Pandemic) - Setiawati, Ririt Iriani Sri; Pusporini, Arin Yuni (Future Science, 2020)
The purpose of this study is to determine the role of the Financial Services Authority in strengthening the Banking Industry in Indonesia during the Covid-19 Pandemic. Qualitative research based on library research is the method used in this research. The type of library research used is textbook analysis. The results of the study show that during the COVID-19 pandemic, OJK has issued several policies to maintain payment traffic flow and financial stability. And the Bank's financial institution